Regular consumption of Fiit-ns, a polyphenol extract from fruit and vegetables frequently consumed within the Mediterranean diet, improves metabolic ageing of obese volunteers: a randomized, double-blind, parallel trial. (28th October 2014) - Cases, Julien; Romain, Cindy; Dallas, Constantin; Gerbi, Alain; Cloarec, Maurice
Abstract: Epidemiological studies suggest that metabolic ageing process of overweight and obese populations is associated with an increased risk of developing non-communicable diseases (NCDs). Inflammation, hyper-glycaemia, dyslipidemia and oxidative stress have been associated with early stages of NCDs development whereas cohort surveys have demonstrated health benefits of dietary polyphenols from various dietary sources to reverse such progress. Obese volunteers were included in a double-blind, randomized, parallel pilot trial where they received daily for a 12-week period 900 mg of a polyphenol-rich treatment extracted from fruit and vegetables frequently consumed within the Mediterranean diet. Anthropometric and blood parameters were assessed before and at the end of the intervention period. After 12 weeks, while the silhouette slimmed down, metabolic parameters were significantly improved and general satisfaction considerably ameliorated. These data suggest that over a 12-week period, the synergistic action of bioactives within the treatment improves metabolic ageing process and quality of life in obese volunteers.